Electrically induced and detected Néel vector reversal in a collinear antiferromagnet. Issue 1 (December 2018) - Godinho, J.; Reichlová, H.; Kriegner, D.; Novák, V.; Olejník, K.; Kašpar, Z.; Šobáň, Z.; Wadley, P.; Campion, R.; Otxoa, R.; Roy, P.; Železný, J.; et al.
Abstract Antiferromagnets are enriching spintronics research by many favorable properties that include insensitivity to magnetic fields, neuromorphic memory characteristics, and ultra-fast spin dynamics. Designing memory devices with electrical writing and reading is one of the central topics of antiferromagnetic spintronics. So far, such a combined functionality has been demonstrated via 90° reorientations of the Néel vector generated by the current-induced spin orbit torque and sensed by the linear-response anisotropic magnetoresistance. Here we show that in the same antiferromagnetic CuMnAs films as used in these earlier experiments we can also control 180° Néel vector reversals by switching the polarity of the writing current. Moreover, the two stable states with opposite Néel vector orientations in this collinear antiferromagnet can be electrically distinguished by measuring a second-order magnetoresistance effect. We discuss the general magnetic point group symmetries allowing for this electrical readout effect and its specific microscopic origin in CuMnAs. Controlling the Néel vector switching is crucial to the antiferromagnetic spintronics but so far limited to 90° reorientations. Here the authors report electrical Néel vector reversal and its detection in a fully compensated collinear antiferromagnet (AF) by exploiting the broken time reversal and spatial inversion symmetries of the AF.